The Exemplary Nature of Prophet Muhammad’s Da’wah as a Model for Noble Character Development of Campus Intellectuals in the Era of Disruption - Ashri Hidayati; Supyan Sauri; Arif Samsudin; Arja Bayirudin (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the implementation of the Prophet Muhammad's da'wah stages as a strategic model for fostering noble character at the Islamic University of Nusantara (Uninus) Bandung. Utilizing a qualitative descriptive approach, data were collected through participant observation, in-depth interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana interactive model. The findings reveal that Uninus adapts three phases of prophetic da'wah: (1) At-Tasqif Murakazzah, focusing on ideological incubation to form a rational Islamic personality; (2) At-Tafa'ul Ma'al Ummah, encouraging students to engage in critical dialectics and social interaction to counter secular hegemony; and (3) Istilamul Hukmi, manifested through the institutionalization of Islamic values in binding campus policies. This study concludes that the integrated prophetic da'wah framework effectively bridges the gap between intellectual and spiritual competence, offering a comprehensive solution for developing Prophetic Intellectuals who are adaptive to the times yet firmly grounded in Islamic values. Keywords: Prophetic Da'wah, Noble Character, Campus Intellectuals, Islamic Education. Abstrak: Penelitian ini bertujuan untuk menganalisis implementasi tahapan dakwah Rasulullah SAW sebagai model strategis pembinaan akhlak mulia di Universitas Islam Nusantara (UNINUS) Bandung. Menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan studi dokumentasi, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldana. Hasil penelitian menunjukkan bahwa UNINUS mengadaptasi tiga fase dakwah kenabian: (1) At-Tasqif Murakazzah yang berfokus pada inkubasi ideologis untuk membentuk kepribadian Islam yang rasional; (2) At-Tafa'ul Ma'al Ummah yang mendorong mahasiswa melakukan dialektika kritis dan interaksi sosial untuk melawan hegemoni sekuler; serta (3) Istilamul Hukmi yang dimanifestasikan melalui institusionalisasi nilai Islam dalam kebijakan kampus yang mengikat. Studi ini menyimpulkan bahwa kerangka dakwah profetik yang terintegrasi efektif menjembatani kesenjangan antara kompetensi intelektual dan spiritual, menawarkan solusi komprehensif untuk melahirkan Intelektual Profetik yang adaptif terhadap zaman namun teguh memegang nilai Islam. Kata Kunci: Dakwah Rasulullah, Akhlak Mulia, Intelektual Kampus, Pendidikan Islam.